Incidence, risk factors, and final causes for misdiagnosis of tuberculosis in the Republic of Korea: a population-based longitudinal analysis. Issue 4 (20th October 2022) - Kim, Changwhan; Ko, Yousang; Moon, Jin-Wook; Park, Yong-Bum; Park, So Young; Ban, Ga-Young; Song, Ju Yeun; Kim, Hajeong; Sim, Yun Su; Park, Ji Young; Lee, Chang Youl
In the Republic of Korea (ROK), the number of notified tuberculosis (TB) cases had not decreased for a long period [1, 2], but decreased remarkably in the past decade following nationwide efforts, including a public–private model, reinforced TB contact investigation, and free TB treatment [3, 4]. In 2020, an overall notification rate of 38.8 per 100 000 persons for new TB cases (n=19 933) was reported, which constituted a 49.6% decrease in the number of cases compared with that notified in 2011 (new cases of TB 39 557; notification rate 78.9 per 100 000 persons for new TB cases) [2]. Misdiagnosis of TB was 7.3% and the trend was unchanged in the 2010s, despite a remarkable decline of TB incidence in the ROK. Misdiagnosis was more common in EPTB than PTB, and risk factors and final causes varied depending on each involved organ system. https://bit.ly/3qnLjJN